2014
DOI: 10.12809/hkmj133942
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery sarcoma diagnosed by endobronchial ultrasound-guided transbronchial needle aspiration

Abstract: Pulmonary artery sarcoma is a rare disease with poor prognosis that has not been reported in Hong Kong. Its clinical and radiological presentation frequently mimics pulmonary embolism. Diagnosis is usually delayed until surgery, which is the treatment option that provides the best survival. Endobronchial ultrasound-guided transbronchial needle aspiration is an effective non-surgical technique for lymph node staging of lung cancer and diagnosis of mediastinal lesions via bronchoscopy. Here we discuss a case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…It is known that collection of tissue samples by fiberoptic bronchoscopy may lead to various complications or adverse reactions ( 21 ). However, in this study, the incidence of complications/adverse reactions in Group A/B/C/D was low, and there were no statistically significant differences in incidences of complications/adverse reactions among the four groups, which is consistent with the findings reported by Chan et al ( 22 ) and Asano et al ( 23 ). Although pneumothorax occurred in 2 patients in Group D (n=234), pneumothorax quantity was only 9.5%.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that collection of tissue samples by fiberoptic bronchoscopy may lead to various complications or adverse reactions ( 21 ). However, in this study, the incidence of complications/adverse reactions in Group A/B/C/D was low, and there were no statistically significant differences in incidences of complications/adverse reactions among the four groups, which is consistent with the findings reported by Chan et al ( 22 ) and Asano et al ( 23 ). Although pneumothorax occurred in 2 patients in Group D (n=234), pneumothorax quantity was only 9.5%.…”
Section: Discussionsupporting
confidence: 92%
“…However, the increasing complications of bleeding have been questioned. 3234 One patient in our series died during the procedure of EBUS-TBNA. Since we did not find active and major bleeding in the airway after biopsy, the possible reason was that the vasospasm of pulmonary artery and the clot formed after the aspiration of the mass obstructed the narrow access in the PT.…”
Section: Discussionmentioning
confidence: 93%
“…The most appropriate procedure to get tissue sample and make a histological diagnosis for patients suspected with PAS still remains to be elucidated and need to be tailored for every single patient. [30][31][32][33][34] Radical surgical resection is still the firstline therapy for PAS, providing the possibility of prolonged survival. 35 Chemotherapy, radiotherapy, and other emerging antineoplastic drugs can be used in combination of surgery to improve clinical outcome of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) can obtain a pathological diagnosis. EBUS-TBNA allows better visualization of the tumor and vascular flow via doppler ultrasonography, [ 42 ] and the obtained cytological materials can be quickly and in-site evaluated to facilitate accurate and early diagnosis of PATs, [ 9 , 43 ] which was speculated to be a minimally invasive and feasible method for assessing intravascular lesions. [ 44 , 45 ] However, it has also been stated that PH caused by occlusive lesions increases the risk of bleeding complications.…”
Section: Pathology Of Tissue Biopsymentioning
confidence: 99%
“…[ 44 , 45 ] However, it has also been stated that PH caused by occlusive lesions increases the risk of bleeding complications. [ 42 , 46 , 47 ] Thus, in the diagnosis of PPATs, the limited sample sizes make the relevant literature less reported, and there is still controversy about the application of this method in the diagnosis of this disease. [ 42 ] Another technique using the endovascular catheter-guided forceps has been able to successfully detect intimal sarcomas of the pulmonary artery in more than 75% of the patients, [ 41 , 48 ] which is an effective and safe diagnostic tool for patients with PPATs.…”
Section: Pathology Of Tissue Biopsymentioning
confidence: 99%